The effect of fuel price increase on transport cost of container transport vehicles - Gohari, A. (GEOMATE International Society, 2018)
This study presents the impact of fuel price increase on the transport cost of containers by using container vehicles. ArcGIS was used to build the transport network while MATLAB software was used to develop Dijkstra's shortest path algorithm and coding the transport cost equation. In this study, two case studies were analyzed with Johor Port as the origin and, the Port Klang and top-north-point were considered as destinations for cases 1 and 2. The optimum routes for each mode of transport were identified. The results of least-cost routes against fuel price increase were compared for shipment of containers from origin to destination in the intermodal network of Peninsular Malaysia. In the analysis, fuel price was increased from its current price sequentially to 100. Based on the assumptions of this study, the results showed that transport cost of a container by train was significantly lower than truck even when the fuel price of the train was doubled. Comparing train-based and ship-based optimal routes revealed that transport cost by train, when its fuel price doubled, was slightly higher than ship in case 1. While in case 2, transport cost by train when its fuel price doubled was considerably cheaper than the ship-based route in its current fuel price. It can be concluded that fuel price increase has the highest impact on transport cost of containers by ship, followed by train and truck. The presented methodology and procedure are applicable for any origin-destination pair in the transport network. Â© 2018, Int. J. of GEOMATE.